Nghiên cứu ảnh hưởng của điều kiện chế tạo đến sự phân bố Pt trong các xúc tác Pt/gamma-Al2O3 - Trịnh, Nguyễn Hữu (Vietnam Journal of Chemistry, 2014)
In the Pt/γ-Al2O3catalysts, the distribution of uniform, small particle-size Pt metal on the carrier with high surface area of metal will result in high catalytic activities and will economize noble metals. The distribution of metal depends on the technology of preparation and post-preparation. The influences of the impregnating, drying, calcining and reducing on the distribution of metal have been studied using by physic methods, scan electronic microscope (SEM), transmission electronic microscope (TEM), and the hydrogen distribution has been measured by the method of hydrogen absorption. The results showed that the samples were impregnated and then dried at 120oC, continously calcined at 200, 300, 400 and 500oC and byusing acidic solvent.